2010
DOI: 10.1038/hr.2010.139
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of assessing masked and white-coat hypertension by ambulatory blood pressure monitoring for determining prevalent risk of chronic kidney disease: the Ohasama study

Abstract: Masked hypertension (MHT) is considered to be associated with organ damage, whereas the association of white-coat hypertension (WCHT) with organ damage remains controversial. Using home blood pressure measurements, we have previously reported that MHT is associated with a risk of chronic kidney disease (CKD) compared with sustained normal blood pressure (SNBP), although WCHT was not significantly related to CKD in a general Japanese population. The objective of this study was to examine CKD risk associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 34 publications
0
20
1
2
Order By: Relevance
“…Its prevalence has been reported to be 13% (10,28) or 18% (29) among the population in general. Bangash and Agarwal performed a meta-analysis of CKD patients (six trials, reported from 2005 to 2008) and reported that the prevalence was 18.3% (10.5%-31.7%) (30) and 15% among CKD cohort (31). Compared with these previous data, the prevalence of WCHT in this study was very low.…”
Section: Discussioncontrasting
confidence: 51%
“…Its prevalence has been reported to be 13% (10,28) or 18% (29) among the population in general. Bangash and Agarwal performed a meta-analysis of CKD patients (six trials, reported from 2005 to 2008) and reported that the prevalence was 18.3% (10.5%-31.7%) (30) and 15% among CKD cohort (31). Compared with these previous data, the prevalence of WCHT in this study was very low.…”
Section: Discussioncontrasting
confidence: 51%
“…It has also been associated with increased risk for cardiovascular and cerebrovascular events [12,13]. However, the effect of masked hypertension on the risk for CKD is less clear as prior studies have been cross-sectional or were conducted among people with established CKD [5,14,15]. In addition, there are few data on the association of masked hypertension on kidney outcomes among African-Americans.…”
mentioning
confidence: 99%
“…One study, albeit small, did demonstrate that patients with masked hypertension and CKD did exhibit an increased risk to the development of end-stage renal disease (ESRD) compared to normotensive patients [12]. Much of the available data, however, relate to the prevalence of masked hypertension in a CKD population [13,14].…”
Section: Cardiovascular and Cerebrovascular Riskmentioning
confidence: 96%